2021
DOI: 10.1016/j.vaccine.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Individual preferences for COVID-19 vaccination in China

Abstract: Background Vaccinations are an effective choice to stop disease outbreaks, including COVID-19. There is little research on individuals' COVID-19 vaccination decision-making. Objective We aimed to determine individual preferences for COVID-19 vaccinations in China, and to assess the factors influencing vaccination decision-making to facilitate vaccination coverage. Methods A D-efficient discrete choice experiment was conducted across six Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
237
5
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(273 citation statements)
references
References 20 publications
28
237
5
3
Order By: Relevance
“…Therefore, interventions targeted at modifying such health beliefs about COVID-19 may lead to improved vaccination rates. The item with the highest OR for vaccine acceptance was 'perceived effectiveness of the COVID-19 vaccine', as reported in some previous studies [15,17]. Additionally, the item with the second highest OR was 'willingness to protect others by getting oneself vaccinated', which was also reported to be one of the important factors associated with COVID-19 vaccine acceptance in a previous study [19], and 489 participants had a low level of willingness to protect others by getting oneself vaccinated.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Therefore, interventions targeted at modifying such health beliefs about COVID-19 may lead to improved vaccination rates. The item with the highest OR for vaccine acceptance was 'perceived effectiveness of the COVID-19 vaccine', as reported in some previous studies [15,17]. Additionally, the item with the second highest OR was 'willingness to protect others by getting oneself vaccinated', which was also reported to be one of the important factors associated with COVID-19 vaccine acceptance in a previous study [19], and 489 participants had a low level of willingness to protect others by getting oneself vaccinated.…”
Section: Discussionsupporting
confidence: 62%
“…Studies on vaccine acceptability of the COVID-19 vaccine were conducted in various countries [14][15][16][17][18][19][20][29][30][31][32][33][34][35][36][37][38]. In Europe, it has been reported that the prevalence of vaccine acceptability was approximately from 60% to 80% [14,[29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their willingness-to-pay (WTP) for COVID-19 vaccines was influenced by social and demographic factors, such as occupation and region. A number of discrete choice experiments revealed that a strong preference for the COVID-19 vaccine depended on its effectiveness, side-effects, protection duration and number of injections [ 14 , 15 , 16 , 17 ]. However, little is currently known about the effect of free vaccinations on the COVID-19 VWR in China.…”
Section: Introductionmentioning
confidence: 99%